Sosialisasi Teknologi Tepat Guna (TTG) untuk Meningkatkan K3 Kualitas dan Produktivitas Konstruksi Melalui Inovasi Portable di PT Gelora - Anwar, Fahri; Romadin, Achmad; Saragi, Alexander Adrian; Aryanugraha, Muh.; Irfan, Andi Muhammad (Jurusan Teknik Informatika dan Komputer, 2025)
Material management problems in construction projects are one of the main factors that affect efficiency, work safety, and environmental sustainability. Unstructured, mixed, and haphazard material arrangement often results in wasteful costs due to damage or loss of materials, slows down the work process due to time wasted sorting materials, and increases the potential for work accidents due to an unorganized environment. In addition, this condition can also cause disturbances to the surrounding community if the project is in a residential area. Based on the problems identified by construction project partners, the solution offered is the implementation of Portable Material on Site Pallet (PMOS), a simple appropriate technology that functions as a storage medium and grouping of construction materials practically and ergonomically. This activity is carried out through the stages of analyzing field conditions, identifying main problems, designing and making portable pallet prototypes, analyzing technical studies, and implementing and evaluating its benefits in the field. The results show that the socialization and implementation of PMOS can improve workers' understanding of safe and efficient material arrangement, reduce potential hazards due to scattered materials, and speed up the work process in the field. The effectiveness of the innovation is also seen from the reduction in material search time from 40 minutes to 5 minutes, with a total work time efficiency of 15.9%. The socialization of TTG has succeeded in triggering the adoption of tools by the project and shows great potential in supporting K3 and construction productivity in a sustainable manner. In addition to simplifying the material logistics process and extending the service life of construction materials, especially for materials such as steel or reinforcing iron that are susceptible to corrosion.